The Effect of Salacca Zalacca Bark Extract on Collagenization and Histopathological of Skin Tissue in Obese Male Mice Wounds - Savira, Luluk Maya; Kartarino, Djamin; Hadi, Lina; Purba, Member Reni (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Collagen regulates wound healing in open and closed skin wounds with its fibrillar structure or as a soluble component. Consume antioxidant-rich vegetables like Salak to fight free radicals and heal. The research aimed to determine the effect of Salak bark extract given to obese rats on accelerating the healing of wounds on the back and to examine the histology of the skin tissue. This type of research is quantitative with a true experiment model. The samples used were Wistar white rats (Rattus norvegicus). The treatment groups of rats were all given distilled water and rat pellet feed, but Salak bark extract was given at different doses per day for 14 days, namely the control group: NaCl 0.9%, and the group was given Salak bark extract at the same dose. Varies per group for mg/kg/BW for Group P1: 300, Group P2: 500, and Group P3: 700. The research data was analyzed using SPSS. In the results of research data processing in the normality test, significant values of p > 0.05 were 0.003 in the control group, 0.102 in P1, 0.078 in P2, and 0.200 in P3. A homogeneity value of 5.024 > 0.05 and an ANOVA value of 0.000 < 0.05 indicate promising results. Salak bark extract at 700 mg/kg BW had the highest collagen density in histological pictures of skin tissue. Salak bark extract contains flavonoids, saponins, tannins, alkaloids, and glycosides, which have antioxidant, antimicrobial, and anti-inflammatory properties and aid wound healing, collagenization, and weight loss in obese mice.